2018
DOI: 10.3832/ifor2553-010
|View full text |Cite
|
Sign up to set email alerts
|

Belowground biomass models for young oligotrophic Scots pine stands in Latvia

Abstract: The increasing interest in carbon budget estimation and the growing use of woody biomass in bioenergy production raises the necessity for precise estimates of belowground biomass and soil carbon pools in forest ecosystems, particularly in terms of changes in the age structure of forests. The aim of this study was to estimate the belowground biomass of young (< 40 years) stands of Scots pine (Pinus sylvestris L.) in Latvia. The biomass of small roots (diameter 2-20 mm), coarse roots (diameter > 20 mm), and stum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Due to its equipment, the theoretical possibilities of using the technique are from the restoration of small drainage ditches to the second commercial thinning. It is possible to calculate the amount of the round wood and wood biomass obtained in pre-commercial and commercial thinning by using algorithms developed for Latvia conditions (Jansons et al, 2017;Kenina et al, 2018;Lībiete et al, 2017;Liepiņš, Lazdiņš, & Liepiņš, 2017) to precisely predict additional revenue from integrated forest management.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its equipment, the theoretical possibilities of using the technique are from the restoration of small drainage ditches to the second commercial thinning. It is possible to calculate the amount of the round wood and wood biomass obtained in pre-commercial and commercial thinning by using algorithms developed for Latvia conditions (Jansons et al, 2017;Kenina et al, 2018;Lībiete et al, 2017;Liepiņš, Lazdiņš, & Liepiņš, 2017) to precisely predict additional revenue from integrated forest management.…”
Section: Introductionmentioning
confidence: 99%
“…The results show a trend in the proportion of belowground biomass, similar to that reported by Parde (1980), in a study carried out in southern Russia with Quercus spp., indicating that roots represent 74% of the total biomass in the former years of life, and then decrease, reaching no more than 21% at ages over 45 years. Kenina et al (2018) found in young stands of Pinus sylvestris L., a higher proportion of belowground biomass in young trees (8-14 years) and a decrease in larger trees (24-40 years). On the contrary, Durkaya et al (2016) and Medrano-Meraz (2018) reported that the proportion of belowground biomass for Pinus sylvestris and P. patula, respectively, increases as the D increases.…”
Section: Biomass Distributionmentioning
confidence: 83%
“…1), which can be explained that the lower and thicker parts of the stem (which was primarily the first fragment) were the heaviest and their weight varied the most. A majority of the biomass models underestimate the actual tree biomass, and their predictions are lower than the real weight (Lībiete et al 2017;Kenina et al 2018). However, the authors' model overestimated the prognosis, as indicated by mean estimated biomass (84.66 ± 4.03 kg, 95% confidence interval).…”
Section: Biomass Distribution Modelmentioning
confidence: 99%